Experimental and modeling analysis of brewers´ spent grains gasification in a downdraft reactor - Ferreira, Sérgio (2019)
The first part of the current reported work presents experimental results of brewers’ spent grains gasification in a pilot-scale downdraft gasifier. The gasification procedure is assessed through various process characteristics such as gas yield, lower heating value, carbon conversion efficiency, and cold gas efficiency. Power production was varied from 3.0 to 5.0 kWh during the gasification experiments. The produced gas was supplied to an internal combustion engine coupled to a synchronous generator to produce electricity. Here, 1.0 kWh of electricity was obtained for about 1.3 kg of brewers’ spent grains pellets gasified, with an average electrical efficiency of 16.5%. The second part of the current reported work is dedicated to the development of a modified thermodynamic equilibrium model of the downdraft gasification to assess the potential applications of the main Portuguese biomasses through produced gas quality indices. The Portuguese biomasses selected are the main representative forest residues (pine, eucalyptus, and cork) and agricultural residues (vine prunings and olive bagasse). A conclusion can be drawn that, using air as a gasifying agent, the biomass gasification provides a produced gas with enough quality to be used for energy production in boilers or turbines.